Raman Spectra and Intermolecular Hydrogen Bonds of Quinoline in Solutions - Tukhvatullin, F.H.; Jumabayev, A.; Hushvaktov, H.; Absanov, A.; Hudoyberdiev, B. (Ukrainian Journal of Physics, 2012)
The half-widths of the 1014- and 1033 cm–1 bands of the Raman spectrum of quinoline at its dilution in neutral solvents (benzene, CCl4) are narrowed by 1.3-1.5 times at high dilutions. This effect is associated with the increased time of the vibrational relaxation. For the 520 cm–1 band in pure liquid quinoline, the parallel polarized component at 20 ºC is asymmetric in the high-frequency region. The shape of the perpendicular polarized component is complicated. A non-coincidence of the peak frequencies of the parallel and perpendicular polarized components is observed (~2 cm–1). Quantum-chemical calculations showed that, in the region of 520 cm–1 for a monomer molecule, we should really have two near located lines with the wavenumbers 530 and 527 cm–1 (scaling factor 0.97), and with the depolarization ratios 0.61 and 0.26. In the solutions with propan-2-ol, the 1033.8 cm–1 band becomes of a doublet character. The resolution of the doublet becomes better by the dilution of a binary quinoline-alcohol solution with a large amount of a neutral solvent (benzene). The wavenumbers of bands in the triple mixture are 1033 cm–1 and 1039 cm–1. The doublet nature of the band in the binary and triple mixtures is associated with the presence of monomer molecules and quinoline-propan-2-ol aggregates (the high-frequency line) in the liquid mixture. Quantum-chemical calculations showed that the hydrogen bonds with a length of 1.958 Å and an energy gain of 22.0 kJ/mole can be formed between molecules of quinoline and alcohol. The formation of aggregates can be also detected in the 820 cm–1 band of propan-2-ol. A similar picture is observed for the 667 cm–1 band of chloroform in its solution with quinoline.